PENGALAMAN KETUBUHAN SEBAGAI KONSTRUKSI TEKSTUR PERTUNJUKAN TEATER KALANGAN REMAJA - Isa Ansari (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2016)
This article aims to provide a description about the existence of a tradition as the realityexperienced by adolescents and presented in a theatrical performance. The quistion is how theJavanese tradition experienced by adolescents and applied in a theatrical performance? Toanswer of this, the reseacher has used Bruner’s theory on the anthropology of experiance anddramatic structure from George Kernodle. Collecting datas is done by observation of differentform of theatre performance by teenegers and interviews to the actors and theatre director.The reseacher conclude that mental disposition and muscle memory was experianced by actorsand directors which is expressed in dialog, mood, and spectacle through theatre performance.Keywords: Javaness tradition, Structur, Mental Disposition.